2021
DOI: 10.1002/ehf2.13072
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognostic value of right ventricular (dys)function in patients with non‐ischaemic dilated cardiomyopathy assessed with cardiac magnetic resonance imaging

Abstract: Aims In non-ischaemic dilated cardiomyopathy (DCM), concomitant right ventricular (RV) dysfunction is frequently observed. This study sought to determine the correlation of RV dysfunction with several cardiac magnetic resonance (CMR) imaging characteristics in patients with DCM, and the prognostic value of RV dysfunction on all-cause mortality and ventricular arrhythmias (VA) was evaluated. Methods and results Consecutive patients with DCM and left ventricular (LV) dysfunction (ejection fraction < 50%) on CMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
2
12
1
1
Order By: Relevance
“…In a retrospective CMR study of 168 patients with dilated cardiomyopathy followed up over a median of 2.2 years, Becker et al. recently showed a link between RV dysfunction and ventricular arrhythmias (but not total mortality) 21 . In contrast, we have found no association between RV volumes or RVEF with the arrhythmic endpoint.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In a retrospective CMR study of 168 patients with dilated cardiomyopathy followed up over a median of 2.2 years, Becker et al. recently showed a link between RV dysfunction and ventricular arrhythmias (but not total mortality) 21 . In contrast, we have found no association between RV volumes or RVEF with the arrhythmic endpoint.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, the multivariate analyses indicated that this association was dependent on LVEF. This is perhaps not unexpected, given the observed correlation between RVEF and LVEF, which has been documented by other CMR studies 20,21 …”
Section: Discussionsupporting
confidence: 75%
“…However, our patient presented with global LV systolic wall motion abnormalities, especially in the LGE segments, revealing an advanced disease stage. It was further confirmed that the extent of myocardial fibrosis was related to poor prognoses, including worsening of LV function and adverse outcomes 14 …”
Section: Discussionmentioning
confidence: 79%
“…It was further confirmed that the extent of myocardial fibrosis was related to poor prognoses, including worsening of LV function and adverse outcomes. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation